The poetics of travel through unravelling visual representations on postcards: A critical semiotics analysis - Christina Bonarou (Journal of Tourism, Heritage & Services Marketing, 2021)
Purpose: Visual representations, as the mechanism of tourism discourses, are vital to the constructed realities of tourism. This paper aims to contribute to ongoing research on tourist postcards and tourist imagery, exploring how contemporary photographic tourist postcards act as narratives of cultural representations and national identities, and how they constitute a 'poetics of travel' by communicating 'myths' about particular destinations. Methods: The methodology has followed the semiotic analysis along with a critical approach, focusing on a corpus of approximately 4,200 picture postcards issued between 2003 and 2019. In addition to adopting a discourse approach, the study can be considered as 'auto-ethnographic' since it analyses the postcards as visual texts of Greece, which have been produced within Greece (by Greek editors and Greek photographers) and as the analysis has been made by a Greek researcher. Results: The findings present some similarities and differences to those outlined in previous exploratory research, and clearly establish that throughout the years contemporary Greece keeps focusing on its self-representation as a historic, authentic and romantic tourist destination; as a the 'cradle of western civilization" and as an "unchanged paradise on earth". Implications: Findings indicate that visual representations as the mechanism of tourism discourses are essential to the constructed realities of tourism, constituting a 'poetics of travel'. The fact that Greece is presented as a 'museum-like' destination, requires, however, special attention because the exaggerated language of the tourist discourse limits Greece in an eternal "unchanged" present, partly cancelling the potential image of modern progress.
Keywords: R41; L83; Z39; 330; visual representations; tourist imagery; semiotic analysis; tourism discourse; postcards; Greece